If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 3x + 2y = 0 Solving X + 3x + 2y = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-3x' to each side of the equation. X + 3x + -3x + 2y = 0 + -3x Combine like terms: 3x + -3x = 0 X + 0 + 2y = 0 + -3x X + 2y = 0 + -3x Remove the zero: X + 2y = -3x Add '-2y' to each side of the equation. X + 2y + -2y = -3x + -2y Combine like terms: 2y + -2y = 0 X + 0 = -3x + -2y X = -3x + -2y Simplifying X = -3x + -2y
| 2(3-x)+7=2x-(x-4) | | 6x+12=12x+6 | | 0.5x+1=2.5x | | 4y-5x=60 | | 8z=2xb | | 12=2(x-4)-6 | | 2(3-x)+7=2x-4(x-4) | | 3(h+4)+5=35 | | (1+x)(1+z)= | | 10x^2+1210=0 | | 2ydx-2xdy=0 | | 18i-14i= | | 5x+-6+2=7x+-6 | | .6k-(k+.25)=.05(k+1) | | Z-4z=9z-9-z | | 2(5-2v)=5(v-5) | | 87-n=13 | | 24n^3+30n^2=0 | | -21a+28a-6=10 | | 4[(12+5)-1024]= | | 5y-15+6=5y+8-1x+17 | | 4x^2+6x+1=2x^2+6x-6+1 | | 8p+5-3=9+7p | | 3(d-2)=15 | | 3s+5w=19 | | 5x-54+3x+16=180 | | 2x^2=x^2-6 | | -4y=-x+6+zy | | 16x^4+32x^3+24x^2+8x-80=0 | | tan(x)=-0.364+0.57735027 | | 6-3u=21 | | n-6=13-4 |